Erotismo e morte em Black Kiss - Rocha Junior, Roberto Wagner (2019)
By presenting some concepts of transgression from eroticism in Howard Chaykin’s Black Kiss comic, this research anchors the debate from the perspectives of Edgar Morín (1973), with the eruption of myth and ritual from anguish towards death; It also absorbs some concepts of instinctual repression of Sigmund Freud (2010); From this point onwards it’s appropriated the concepts of interdiction, transgression and eroticism in the philosophy of Georges Bataille (1987). The first chapter approaches language and technology based on the concepts of Marcelo Dascal (2002) and Ernst Cassirer (2001). Technology is approached from the vision of Álvaro Vieira Pinto (2005) and the phenomenological critique presented by Alberto Cupani (2004). From then on a brief history of pornography and its transformations according to the historical moment and technological possibilities from Lynn Hunt (1999). In the next chapter it is necessary to contextualize the erotic and the transgressive in American comics context after the Comic Code Authority. To this end, we briefly review the history of graphic novels in the West and their influences. Next, in chapter three, it’s presented the concepts of eroticism and transgression from Freud (2010) and Bataille (1987). Finally, in the last chapter, far from exhausting the theme, some examples of transgression and eroticism are presented in Howard Chaykin’s Black Kiss comic.